Smart grid technologies in electric power supply systems of public transport - Bartłomiejczyk, Mikołaj (Transport, 2018)
Nowadays the issue of electric energy saving in public transport is becoming a key area of interest which is connected both with a growth in environmental awareness of the society and an increase in the prices of fuel and electricity. It can be achieved by improving the usage of regenerative breaking. In 2016 the Przedsiębiorstwo Komunikacji Trolejbusowej (PKT, Trolleybus Transport Company) in Gdynia began practical implementation of Smart Grid solutions within its trolleybus network. These activities constitute an element of the project ELIPTIC, realised by PKT within the scientific research fund Horizon 2020. The first stage of implementing intelligent network solutions was completed in 2016, and further activities are planned for the next few years. This paper presents a review of Smart Grid solutions which can be implemented in urban traction supply systems, describes the PKT experience concerning the implementation of Smart Grid solutions in trolleybus network supply system to date.